Mexico : The IOSCO Objectives and Principles of Securities - International Monetary Fund; World Bank (World Bank, Washington, DC, 2014)
As the supervisor of the securities markets in Mexico, the National Banking and Securities Commission (Comision Nacional Bancaria y de Valores, CNBV) has developed a robust supervisory framework that exhibits high levels of implementation of the International Organization of Securities Commissions Objectives and Principles of Securities Regulation (IOSCO Principles) in many areas. The assessment was conducted during the International Monetary Fund (IMF) and World Bank Financial Sector Assessment Program (FSAP) mission to Mexico during the period September 7 to September 21, 2011. The assessment was carried out using the 2003 IOSCO methodology for assessing implementation of the IOSCO Principles. The most significant issues regarding full implementation of the Principles fall under the regulator principles. These issues flow from two sources. First, there is no specific statute governing derivatives (whether exchange traded or over-the-counter (OTC)), nor any other express legislative provisions that govern the regulation of that growing market. Second, there are significant weaknesses in the protections afforded members of the Board of Governors and staff and with the resources of the commission that lead to concerns about its independence and ability to carry out its mandate fully. This report gives summary of discussions on CNBV acceptance to allow the informal assessment of the status of implementation of the newly added Principles, using the guidance provided in the draft revised assessment methodology as issued in May 2011.